Dynamic Simulation and Validation of a Vent and Safety Valve for Cryogenic Flight Tanks. (2016) - Manimaran, A.; Hiremath, Somashekhar S.; Shekhar, K. Panuganti
Abstract: High Thrust Cryogenic Rocket Stages entail the use of a Vent and Relief Valve which can cater to a higher discharge rate. The Vent function is called for during ground servicing operations like tank chilling and pressurant replenishment and during flight to take care of the decrease in ambient pressure and boil-off losses. The Relief function acts as a redundant feature to protect the tanks from catastrophic failure due to structural damage caused by over-pressurization. Nevertheless, this valve needs to be characterized for both these functions during ground tests. This paper describes the modelling of and experimentation on an Inverted Type Pilot Operated Vent and Safety Valve. A mathematical model for simulating the dynamic behavior of this tank-mounted valve is developed. For this, a set of non-linear, first order, coupled ordinary differential equations, based on laws of conservation of mass and energy, are derived using fixed control volume approach. The numerical solution of these equations is obtained using fourth order Runge-Kutta method. The pressure, temperature, flow rate, seat stress and lift thus obtained are plotted to find the characteristic parameters such as cracking pressure, full flow pressure, reseal pressure, opening and closing response, tank pressure decay rate and full flow rate. The valve performance is studied for the effect of main valve outlet orifice and the pilot valve outlet orifice using these simulations. These results are validated by comparing it to the test results.